PROJECT BASED LEARNING INTEGRATED TO STEM TO ENHANCE ELEMENTARY SCHOOL’S STUDENTS SCIENTIFIC LITERACY - Afriana, J.; Permanasari, A.; Fitriani, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
This study was done to depict Project Based Learning (PjBL) integrated with science science, technology, engineering, and mathematics (STEM), to enhance elementary school students’ science literation. Theme used in this study was air pollution. Research method was quasi experimental with The Matching-Only Pretest-Posttest Control Group Design. It was conducted in 56 seventh graders of SMP Islam Terpadu, Sukabumi in which 28 students were in experiment class, and 28 students were in control class. Data is collected by pretest and posttest of sciences literacy and students questionaire about PjBL STEM. Based on the data analysis, it was known that the N-Gain averages of sciences literacy were 0,31 in experiment class as middle category and 0,22 in control class as low category. T-test showed that scientific literacy enhancemen in experimental class was more significant than in control class. General students’ reponses showed that almost all students was excited to PjBL STEM learning, got impressive experiences during the learning and boost their learning motivation and interest.